Smooth muscle myosin mutants containing a single tryptophan reveal molecular interactions at the actin-binding interface - Yengo, C. M. (The National Academy of Sciences, 1998)
Elucidation of the molecular details of the cyclic actomyosin interaction requires the ability to examine structural changes at specific sites in the actin-binding interface of myosin. To study these changes dynamically, we have expressed two mutants of a truncated fragment of chicken gizzard smooth muscle myosin, which includes the motor domain and essential light chain (MDE). These mutants were engineered to contain a single tryptophan at (Trp-546) or near (Trp-625) the putative actin-binding interface. Both 546- and 625-MDE exhibited actin-activated ATPase and actin-binding activities similar to wild-type MDE. Fluorescence emission spectra and acrylamide quenching of 546- and 625-MDE suggest that Trp-546 is nearly fully exposed to solvent and Trp-625 is less than 50% exposed in the presence and absence of ATP, in good agreement with the available crystal structure data. The spectrum of 625-MDE bound to actin was quite similar to the unbound spectrum indicating that, although Trp-625 is located near the 50/20-kDa loop and the 50-kDa cleft of myosin, its conformation does not change upon actin binding. However, a 10-nm blue shift in the peak emission wavelength of 546-MDE observed in the presence of actin indicates that Trp-546, located in the A-site of the lower 50-kDa subdomain of myosin, exists in a more buried environment and may directly interact with actin in the rigor acto-S1 complex. This change in the spectrum of Trp-546 constitutes direct evidence for a specific molecular interaction between residues in the A-site of myosin and actin.